Anxiety among Medical Students when Faced with the Practice of Anatomical Dissection. Issue 3 (30th October 2018) - Romo Barrientos, Carmen; José Criado‐Álvarez, Juan; González‐González, Jaime; Ubeda‐Bañon, Isabel; Saiz‐Sanchez, Daniel; Flores‐Cuadrado, Alicia; Luis Martín‐Conty, José; Viñuela, Antonio; Martinez‐Marcos, Alino; Mohedano‐Moriano, Alicia
Abstract : Practical training in the dissection of human cadavers is a fundamental and traditional component of human anatomy education in medical schools. This practice, however, can be stressful for students and can generate a certain amount of anxiety. The aim of this study is to explore the attitudes, reactions, and anxiety levels of first‐year medical students when working in the dissecting room, over a period of one year, and to relate these anxiety levels to the results of our educational program. This is a before and after descriptive study of students at the University of Castilla‐La‐Mancha. Questionnaires were distributed among them before and after their dissection practices in order to understand their feelings and emotions and their satisfaction about this activity. State‐Trait Anxiety Inventory questionnaires were used to assess the students' 'state anxiety' (SA), which dropped significantly from 49.1% to 14% by the end of their first year. Female students started with higher levels of SA than their male counterparts but by the end of the year these had dropped to similar levels. Anxiety and fearful thoughts tended to drop ( P  > 0.05). In contrast, uncertainty levels showed significant changes, falling from 44.4% to 12.3%. Nonetheless, 100% of students would go through the experience again. Indeed, 98.2% considered that dissection practices were useful in reinforcing the theoretical aspects of their education, and 80.7% believed that dissecting was more useful than theoretical models. Although students were satisfied with dissection practices the experience cause stressful responses.